An Analysis of Sisters in Islam’s (SIS) Misinterpretation of the Gender Equality in the Quran - Norzulaili Mohd Ghazali; Robiatul Adawiyah Mohd @ Amat; Mohd Zohdi Mohd Amin; Nadzrah Ahmad (USIM Press, 2024)
Vol. 16 No. 2 (2020): Journal of Maʿālim al-Qurʾān wa al-Sunnah